Advanced Processing and Manufacturing Technologies for Structural and Multifunctional Materials VII : a collection of papers presented at the 37th International Conference on Advanced Ceramics and Composites, January 27-February 1, 2013, Daytona Beach, Florida - International Conference on Advanced Ceramics and Composites 2013 : Daytona Beach, Fla.); Ohji, T. (Tatsuki); Singh, M. (Mrityunjay); Kirihara, Soshu; Widjaja, Sujanto; American Ceramic Society (Hoboken : Wiley, 2014)
A collection of 20 papers from The American Ceramic Society's 37th International Conference on Advanced Ceramics and Composites, held in Daytona Beach, Florida, January 27-February 1, 2013. This issue includes papers presented in the 7th International Symposium on Advanced Processing and Manufacturing Technologies for Structural and Multifunctional Materials and Systems (Symposium 8).
Includes author index.
Includes bibliographical references and index.
Online resource; title from PDF title page (Wiley, viewed April 8, 2014).
Keywords: Ceramic materials -- Congresses; Composite materials -- Congresses; Manufacturing processes -- Congresses; Ceramics; GARDENING -- Fruit; TECHNOLOGY & ENGINEERING -- Agriculture -- General; Ceramic materials; Composite materials; Manufacturing processes; Electronic books; Conference papers and proceedings